Responsibility in mass communication - Schramm, Wilbur, 1907-1987. (New York : Harper, 1957)
"As background he traces the historical development of the technics of communication from the invention of printing through the power press, telegraph, movies, radio, and television. He then discusses four major concepts of communication -- authoritarian, totalitarian, libertarian, and social responsibility."
Bibliography: p. 370-374. Bibliographical references included in "Notes" (p. 375-384).
HU OSA 300 - RFE/RL collection
Keywords: Mass media -- Social aspects